2023
DOI: 10.1038/s41467-023-38030-6
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-6 mediates the uptake of extracellular vesicles through a noncanonical glycolipid binding pocket

Abstract: Immunomodulatory Siglecs are controlled by their glycoprotein and glycolipid ligands. Siglec-glycolipid interactions are often studied outside the context of a lipid bilayer, missing the complex behaviors of glycolipids in a membrane. Through optimizing a liposomal formulation to dissect Siglec–glycolipid interactions, it is shown that Siglec-6 can recognize glycolipids independent of its canonical binding pocket, suggesting that Siglec-6 possesses a secondary binding pocket tailored for recognizing glycolipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 75 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Asialoglycans exhibited no statistically significant binding to SNA-I and CD22 proteins or CD22 + cells at any density. We previously confirmed that decrease of lectin–glycan interactions at high glycan density occurs due to steric occlusion 38 , 61 , here we tested this again by making a phage that displayed a mixture of sialylated and non-sialylated glycans (Supplementary Fig. 41 ).…”
Section: Resultsmentioning
confidence: 53%
“…Asialoglycans exhibited no statistically significant binding to SNA-I and CD22 proteins or CD22 + cells at any density. We previously confirmed that decrease of lectin–glycan interactions at high glycan density occurs due to steric occlusion 38 , 61 , here we tested this again by making a phage that displayed a mixture of sialylated and non-sialylated glycans (Supplementary Fig. 41 ).…”
Section: Resultsmentioning
confidence: 53%
“…55 To explain the variation in binding profiles observed with the different methods, it was proposed that not only affinity but other factors are important for the detection of these interactions, such as steric crowding and the differing presentation of interactions in solution and in a lipid bilayer. 55 To more firmly establish the ganglioside binding properties of Siglec-1, MEAN-nMS was performed using a DBCO-labeled small monomeric Siglec-1 fragment, consisting of its first three extracellular domains, and the panel of ganglioside-containing NDs described above. Notably, signal corresponding to the 1:1 complex of the membrane anchor-linked Siglec-1 bound to each of the gangliosides was detected (Figures 2c,d, 3c, and S10), with F GSL ranging from 0.5 to 0.8.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, the specificities of human Siglecs 1-11 and -15 for gangliosides were profiled using four different assays . Binding data for a soluble dimeric Siglec-1-Fc fusion complexed with tetrameric Strep-Tactin horseradish peroxidase conjugate measured with a lipid bilayer-free ELISA suggested that all nine gangliosides tested (GM1, GM2, GD1a, GD1b, GD3, GT1b, GM3, GM4 and GQ1b) are ligands, with GM2 and GM3 exhibiting the strongest avidities .…”
Section: Resultsmentioning
confidence: 99%
“…These EVs can be classified into three primary subtypes, namely microvesicles, EXOs, and apoptotic bodies. EVs are responsible for encapsulating cell-derived contents and mediating intercellular communication locally and over long distances transportation of functional substances, including RNA, DNA, proteins, and lipids [ 28 , 29 ]. These entities have the potential to serve as biomarkers, therapeutic agents, and drug delivery vehicles [ 30 ].…”
Section: Discussionmentioning
confidence: 99%